Comparative Analysis of Religious Education in Turkey and Indonesia - Hidayah Hariani; Firda Nur Jannah; Arrijal Abdul (Jurnal Studi Agama, 2022)
This paper examines religious education in two countries; Turkey and Indonesia with the aim of knowing the similarities and differences in religious education from the two countries. This research is field research using a comparative approach. Research data obtained from interviews, observation and documentation. Meanwhile, in analyzing the data used descriptive-comparative technique. This research found that religious education in Turkey and Indonesia have similarities, that is, both are implemented in private or non-government educational institutions. However, there are significant differences between the two countries, in Indonesia religious education can be held by any institution, both in private and public educational institutions and exists at any level from basic education to higher education, whereas in Turkey religious learning is only in private education, private sector and not found at the level of basic education to higher education except at the ushuluddin or divineyat faculties.